English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Add:
(-15rs + rst ) + (5rs - rst )

Subtract:
(7c - d) - (3c - 2d)

2007-05-29 08:24:28 · 9 answers · asked by jfinlinson@att.net 1 in Science & Mathematics Mathematics

9 answers

1. (-15rs + rst ) + (5rs - rst)

First: eliminate parenthesis - rewrite the expression.

-15rs + rst + 5rs + (- rst)
-15rs + rst + 5rs - rst

Sec: combine "like" terms.

-15rs + 5rs + rst - rst
-10rs + 0rst
-10rs

2. (7c - d) - (3c - 2d)

First: eliminate parenthesis - rewrite the expression.

7c - d - (3c) - (- 2d)
7c - d - 3c + 2d

Sec: combine "like" terms.

7c - 3c - d + 2d
4c + d

2007-05-29 09:59:47 · answer #1 · answered by ♪♥Annie♥♪ 6 · 0 0

The first problem: (-15rs + rst ) + (5rs - rst )
Remove the parentheses: -15rs + rst + 5rs - rst
Rearrange terms: -15rs + 5rs + rst - rst
Combine similar terms: -10rs + 0 = -10rs

You can solve the second problem the same way.

2007-05-29 15:29:47 · answer #2 · answered by morningfoxnorth 6 · 0 0

(-15rs +rst) + 5rs - rst
15rs + rst + 5rs -rst
15rs + 5 rs
20rs

(7c -d) - (3c - 2d)
7c -d -3c + 2d
4c + d

http://www.coolmath.com
"like terms"
Terms are separated by + and -.
Like terms have the same letters with the same exponents.

2007-05-29 15:33:15 · answer #3 · answered by Anonymous · 0 0

The parentheses are meaningless in this context. Just eliminate them. Then add the terms that are alike.
-15rs + 5rs + rst -rst = -10rs
7c - 3c - d + 2d = 4c + d

Or you could view it like this
-15rs + rst
5rs - rst
----------------
-10rs + 0rst

2007-05-29 15:28:53 · answer #4 · answered by dogsafire 7 · 1 0

-15rs + rst + 5rs -rst = -15rs + 5 rs + rst - rst = -10rs
7c - d - 3c -(-2d) = 7c - 3c -d + 2d = 4c + d

2007-05-29 15:49:31 · answer #5 · answered by skipper 7 · 0 0

(-15rs + rst ) + (5rs - rst )

= -15rs + rst + 5rs - rst

= -10rs

(7c - d) - (3c - 2d)

= 7c - d - 3c + 2d

= 4c + d

2007-05-29 15:29:05 · answer #6 · answered by Wal C 6 · 1 0

(-15rs + rst ) + (5rs - rst )=(-15rs + 5rs ) + (rst - rst )= -10rs
(7c - d) - (3c - 2d)=7c - d - 3c + 2d = (7c - 3c)+ ( -d+ 2d)=4c+d

2007-05-29 15:30:15 · answer #7 · answered by pioneers 5 · 0 0

Add or subtract "things" that are the same:-
Question 1
- 10 rs
Question 2
= 4c - d + 2d
= 4c + d

2007-05-29 17:37:05 · answer #8 · answered by Como 7 · 0 0

-10rs

4c+d

2007-05-29 15:29:55 · answer #9 · answered by Cool Nerd At Your Service 4 · 0 1

fedest.com, questions and answers